Non-point source fecal contamination from aging wastewater infrastructure is a primary driver of antibiotic resistance in surface waters. (15th August 2022) - Damashek, Julian; Westrich, Jason R.; McDonald, Jacob M. Bateman; Teachey, Morgan E.; Jackson, Charlene R.; Frye, Jonathan G.; Lipp, Erin K.; Capps, Krista A.; Ottesen, Elizabeth A.
Highlights: Widespread correlation of antibiotic resistance genes and human fecal pollution. Novel synthesis of qPCR and geospatial data to identify contamination sources. Sewers and aging septic systems are primary drivers of contamination. Highlights role of non-point sources of antimicrobial resistance to surface waters. Abstract: Antibiotic resistance is a global threat to human health. Many surface water resources are environmental hotspots of antibiotic resistant gene (ARG) transfer, with agricultural runoff and human waste highlighted as common sources of ARGs to aquatic systems. Here we quantified fecal marker genes and ARGs in 992 stream water samples collected seasonally during a 5-year period from 115 sites across the Upper Oconee watershed (Georgia, USA), an area characterized by gradients of agricultural and urban development. Widespread fecal contamination was found from humans (48% of samples), ruminants (55%), and poultry (19%), and 73% of samples tested positive for at least one of the six targeted ARGs ( ermB, tet (B), bla CTX-M-1, bla KPC, bla SHV, and qnrS ). While ARGs were strongly correlated with human fecal markers, many highly contaminated samples were not associated with sewage outfalls, an expected source of fecal and ARG pollution. To determine sources of contamination, we synthesized ARG and fecal marker data with geospatial data on land use/land cover and wastewater infrastructure across the watershed. This novel analysis found strong correlations between ARGs and measures of sewer density, sewer length, and septic system age within sample watersheds, indicating non-point sources of fecal contamination from aging wastewater infrastructure can be critical disseminators of anthropogenic ARGs in the environment. Graphical Abstract: Image, graphical abstract